Pengaruh Media Pembelajaran Visual Dan Audiovisual Serta Gaya Kognitif Terhadap Hasil Belajar Siswa - Yusnidah Yusnidah; Taruna Taruna (JKTP: Jurnal Kajian Teknologi Pendidikan, 2021)
This study aims to determine differences in student learning outcomes based on cognitive aspects in terms of the use of learning media, differences in student learning outcomes in terms of cognitive style, the interaction between student learning outcomes based on cognitive aspects in terms of the use of learning media and cognitive styles. The sample was determined using random sampling where the first class as the experimental class used interactive learning media and the second class as the control class applied conventional learning. The instrument used in this study was a cognitive style instrument consisting of 10 questions and an instrument for student learning outcomes in electronics lessons consisting of 15 questions which were declared valid and reliable. The results showed that, student learning outcomes based on cognitive aspects in terms of the use of audiovisual learning media were better than student learning outcomes using visual media, the learning outcomes of students who have a field independent cognitive style are better than students who have a field dependent cognitive style, there is no interaction between student learning outcomes based on cognitive aspects in terms of the use of learning media and cognitive styles.AbstrakPenelitian ini bertujuan untuk mengetahui perbedaan hasil belajar siswa berdasarkan aspek kognitif ditinjau dari penggunaan media pembelajaran, perbedaan hasil belajar siswa ditinjau dari gaya kognitif, interaksi antara hasil belajar siswa berdasarkan aspek kognitif ditinjau dari penggunaan media pembelajaran dan gaya kognitif. Sampel ditentukan menggunakan random sampling dimana kelas pertama sebagai kelas eksperimen menggunakan media pembelajaran dan kelas kedua sebagai kelas kontrol diterapkan pembelajaran konvensional. Instrumen yang digunakan pada penelitian ini adalah instrumen gaya kognitif terdiri dari 10 pertanyaan dan instrumen hasil belajar siswa pada pelajaran elektronika yang terdiri dari 15 pertanyaan yang dinyatakan valid dan reliabel. Hasil penelitian menunjukkan bahwa hasil belajar siswa berdasarkan aspek kognitif ditinjau dari penggunaan media pembelajaran audiovisual lebih baik dibandingkan hasil belajar siswa yang menggunakan media visual, hasil belajar siswa yang memiliki gaya kognitif field independent lebih baik dibandingkan siswa yang memiliki gaya kognitif field dependent, tidak terdapat interaksi antara hasil belajar siswa berdasarkan aspek kognitif ditinjau dari penggunaan media pembelajaran dan gaya kognitif.